STUDIES OF SOCIOLINGUISTICS: THEORY OF POLITENESS IN ENGLISH AS SECOND LANGUAGE - Asti Gumartifa (UIBU, 2022)
In the social study of language, linguistic politeness has played a central role. Politeness in speaking English is also part of sociolinguistic and pragmatic learning. Each country has a variety of cultures and language accuracy in communication. Unfortunately, most learners don’t speak English based on the sociolinguistics features and it is influenced by the culture, gender, language style, and domain. Therefore, there are still some issues to the practice of politeness linguistics to the English as a second language. The study of qualitative research was used in this study method. The purposes of this research are to inform eight theories of politeness application, the concept of face in politeness, and various types of politeness which are also explained by the division and classification of politeness. To support the students’ information about politeness in linguistics, some existing research information is discussed in this research.